Reflexiones y aproximaciones en torno a los sistemas políticos en el periodo prehispánico en el altiplano puneño - Ramos, Roberto (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2022)
This article is a reflection and brief approach from archaeology, anthropology and political science on the theory and history of political ideas in their development version of political forms or political systems in pre-industrial societies that developed in the basin. north of Titicaca.